Civil-Military Relations in the season of military populism: Czechia - Frič, Pavel; Pernica, Bohuslav (My University, 2024)
The influx of populism in Europe revived the values of illiberal, authoritarian government. This affects the democratic character of Civil–Military Relations (CMR) in the post-communist countries in particular. We analyzed the development of CMR in Czechia (1992–2022) under the influence of populism (2010–2022). Applying the CMR concept of the shared-democratic-values-perspective, our study provides empirical evidence that persistent shortcomings in formal institutional and informal socialization of Czech officers by values of democracy open a dangerous back door for spreading the values of military populism in the Czech Armed Forces. We argue that such development in the last 10 years has resulted into a formation of illiberal alliances between populist leaders and the military elite and poses a risk of the army being misused to politically support the authoritarian populist government.
Civilně-vojenské vztahy v době vojenského populismu: Česká republika
Keywords: civil–military relations; shared-democratic-values-perspective; military elite; socialization, professional military education; civilně-vojenská vztahy; perspektiva společně sdílených demokratických hodnot; vojenská elita; socializace; profesní vojenské vzdělávání